(untitled) - Petroutsos, Evangelos (Indianapolis, Ind., 2006)
This book offers expert assistance that makes it even easier. Inside, two veteran Visual Basic developers show you how to do everything Express Edition makes possible--and even a few things, such as Office development.
Keywords: BASIC (Computer program language); Ngôn ngữ lập trình máy tính